Intrastromal antifungal injection as a successful modality of treatment for fungal keratitis: a case series - Maniam, Anita; Yuen, Goh Siew (International Journal of Research in Medical Sciences, 2018)
Fungal keratitis is a dreaded occurrence in the cornea and anterior segment given the difficulty in treating the disease. Hereby reporting 5 cases of fungal keratitis causes by virulent organisms such as Aspergillus versicolor, Aspergillus fumigatus, Phialophora sp, and Fusarium sp. A retrospective interventional case series of 5 fungal keratitis which were successfully treated by intrastromal antifungal injection performed by a single surgeon from March 2017 till April 2018. The fungal keratitis stromal abscess sizes range from largest of 3mm x 2mm to smallest of 1mmx 1mm, mostly located paracentral and one case was noted to have hypopyon measuring about 1mm. On the first week of treatment, patients noted to exhibit poor response to topical antifungal. Hence, intrastromal amphotericin B injection 5mcg/0.1ml about 0.1ml administered into the affected eye ranging from once to 3 times in all patients except for one patient; who is post-operative 1 year penetrating keratoplasty infected with Phialophora keratitis is given intrastromal amphotericin B injection 5mcg/0.1ml about 0.1ml for 3 times and intrastromal voriconazole injection 50mcg/0.1ml about 0.1ml for 3 times. Within next four weeks, all the 5 cases of fungal keratitis became completely quiet with healed epithelial defect and corneal scarring. In summary, the intrastromal antifungal injection can constitute a good modality for the treatment of recalcitrant cases of fungal keratitis, revealing highly potent antifungal effects as the medication is administrated directly to the site of keratitis, promises shorter recovery period, and early intrastromal antifungal injection also leads to quicker healing with good vision prognosis.